Enlarged vestibular aqueduct: Intraoperative electrocochleography findings during cochlear implantation. (July 2020) - Riggs, William J.; Hiss, Meghan M.; Varadarajan, Varun V.; Mattingly, Jameson K.; Adunka, Oliver F.
Abstract: Enlarged vestibular aqueduct (EVA) is the most frequent inner ear abnormality found on computed tomography in children with sensorineural hearing loss. The effects EVA abnormalities have on electrocochleography (ECochG) are unknown. Positive deflections in summation potential evoked by tone bursts were observed in 3/5 subjects, while a large negative deflection, similar to endolymphatic hydrops (EH), was observed for 2/5 subjects. The presence of an enlarged summation potential, with and without a compound action potential, was observed in response to a broadband click stimulus. Results suggest likely effects of a third window on ECochG responses and presence of EH in EVA.